Desktop application for crypto-protected voice communication - Ivanović, Stefan М.; Marković, Marko R.; Stanišić, Sava S.; Živanović, Kristina R.; Kolašinac, Dimitrije S. (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: All data exchanged over the Internet as well as other computer networks should be considered exposed to various types of security threats. In light of this, the transmission of voice over applications that do not use any type of crypto-protection allows anyone to discern the content of communication. Since voice transmission requires as little delay as possible, various protocols are used to enable crypto protected real-time communication. This paper presents one solution in a desktop application variant.Methods: The essence in voice exchange systems as well as in other systems where real-time communication is necessary is the establishment of a crypto-protected session which is a virtual secure channel for communication to which only the communicating parties have access.  Voice sessions in the application are established with the SIP (Session Initiation Protocol) protocol. The sessions are further protected using the ZRTP (Zimmerman Real-time Transport Protocol) protocol. FusionPBX was used  as the SIP server (registrar) for testing purpouses. The application is developed in C++ language using the Qt framework.Results: The final version of the application demostrates that ZRTP and SIP protocols are well suited for establishing crypto protected voice communications with low delay.Conclusion: This   solution  provides   cryptographic   functions    for    data secrecy and the management of cryptographic keys. Improving the solution with digital signatures and certificates will result in additional cryptographic functions: data integrity and personal identification. With this improvement, this solution will be able to withstand modern security threats with low delay.
Keywords: crypto protected sessions; real-time communication; voice sessions; SIP protocol; ZRTP protocol; communications